FACTORS RELATED TO ANXIETY LEVEL AMONG PROFESSIONAL PROGRAM STUDENTS AT THE FACULTY OF MEDICINE, HASANUDDIN UNIVERSITY DURING THE COVID-19 PANDEMIC - Ismail, Muhammad Wirasto; Syamsuddin, Saidah; Arman, Arman (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2025)
COVID-19 has caused health problems, including stress or anxiety among the general public, health workers and students. Anxiety disorders related to COVID-19 have been reported with a high prevalence. Professional Program Medical Students (PPMS), as part of the groups in direct contact with patients in hospitals during the pandemic, are also affected. This research used a descriptive correlational design with a quantitative approach. Generally, this study aims to identify the factors that influence anxiety level among PPMS, or medical students, of Faculty of Medicine at Hasanuddin University during the COVID-19 pandemic. Specifically, it examines demographic and clinical factors associated with anxiety. The results showed that 53.1% of students did not experience anxiety, while 46.9% reported mild to severe anxiety. Significant factors influencing anxiety included gender, number of friends, and psychiatric history. In contrast, age, marital status, COVID-19 history, academic level, and Personal Protective Equipment (PPE) availability did not significantly affect anxiety levels. Keywords: anxiety, COVID-19, GAD, Medical students DOI : 10.35990/mk.v8n4.p389-399